Substrate pH mediates growth promotion and resilience to water stress of Tilia tomentosa seedlings after Ectomycorrhizal inoculation - Cindy Serafim; Miguel A. Ramos; Tugce Yilmaz; Nadine R. Sousa; Kang Yu; Maarten Van Geel; Tobias Ceulemans; Marc Saudreau; Ben Somers; Thierry Améglio; Olivier Honnay; Paula M. L. Castro (BMC Plant Biology)
Highlights Urban trees in urban environments are commonly exposed to stresses, contributing to their health decline; Ectomycorrhizal fungi improve the vigour and resilience of Tilia seedlings, but their performance is dependent on soil pH. Inoculation promotes growth in height, biomass production, mycorrhization status, nutrient uptake, and proline accumulation, and these effects dependent on fungi species and soil pH; Inoculation with EcM can be a strategy to produce healthier saplings that when transplanted to the urban environment will have a better performance.